STAGES AND FEATURES OF NEW SOCIAL CONSCIOUSNESS FORMATION IN THE PROCESS OF NATIONAL RENAISSANCE - Berdikulova Surayyo Aslamovna (Modern American Journals, 2025)
This article explores the philosophical foundations of changes in social consciousness, analyzing how transformations in societal values, norms, and collective thinking reflect broader historical, cultural, and technological shifts. The study discusses the dialectical relationship between material conditions and consciousness, highlighting the influence of globalization, digitalization, and ideological narratives on public perception. Special attention is given to the role of education, media, and social institutions in shaping collective awareness. The research concludes that understanding changes in social consciousness is essential for effective policy-making, national development, and preserving cultural identity in the modern world.
Keywords: Social consciousness, philosophy, change, society, collective thinking, values, ideology, globalization, digital transformation, public awareness, education, cultural identity.